STRATEGI GURU DALAM MENGELOLA PEMBELAJARAN KELAS BILINGUAL PADA MATA PELAJARAN BAHASA INDONESIA KELAS 3 MADRASAH IBTIDAIYAH NEGERI 2 LAMONGAN - Eka Aprilia Salsabila; Lusi Aini Avrilia; Irma Jayanti; Lutfatin Nihaya; Retno Nuzilatus Shoimah (STKIP Subang, 2026)
This study aims to examine teachers' strategies in managing bilingual classroom learning in Indonesian language subjects for third graders at Madrasah Ibtidaiyah Negeri 2 Lamongan. The research method used is a descriptive qualitative approach with a case study design. Data collection was conducted through observation, in-depth interviews, and documentation to obtain a comprehensive picture of bilingual learning practices. The results of the study indicate that teachers face major challenges in the form of limited foreign language skills and managing bilingual classroom interactions. Teachers implement various strategies such as the use of contextual language, practice-based learning, and utilizing the school environment as a learning resource. These strategies have been proven to increase student activeness, understanding, and motivation in learning Indonesian. The discussion shows that this strategy is important to implement because bilingual learning requires a balance between mastery of the mother tongue and a foreign language to avoid hindering students' literacy development. In addition, the contextual approach was chosen because it can create meaningful, enjoyable, and relevant learning experiences with students. The conclusion of the study shows that effective management of bilingual learning requires language competence, pedagogical skills, and teacher creativity. Therefore, it is recommended that ongoing training for teachers and school policy support be provided to improve the quality of bilingual learning in madrasahs.